A new species of the Ophiocordyceps (Ophiocordycipitaceae, Hypocreales) from Jilin Province, China - Wang, Yu; Bau, Tolgor (Phytotaxa, 2026)
Based on morphological and molecular phylogenetic analyses, a new species of Ophiocordyceps from China is described: Ophiocordyceps changbaishanensis sp. nov. The species is characterized by a predominantly solitary and unbranched stroma. The fertile part is ellipsoid to cylindrical, with a slightly acute apex and longitudinal striations on the surface, greyish-yellow to olivaceous at the tip. The perithecia are large, long-ampulliform, and obliquely immersed. The ascus apex is obcordate and distinctly thickened. Ascospores are filiform, disarticulating at maturity into fusoid secondary ascospores measuring 10.3–15.6 × 1.8–3.2 μm. Phylogenetic analyses based on the combined sequences of ITS, nrLSU, tef1-α, rpb1, and rpb2 demonstrate that this new species is phylogenetically distinct from other known species within the Ophiocordyceps sphecocephala clade. Detailed descriptions and line drawings are provided.